DIGITAL PAYMENTS AND MSMES' FINANCIAL PROFILES FOR BANK FINANCING - Hendri Mauliansyah; Abdul Aziz; Rusnaidi (GLOBAL RESEARCH IN ECONOMICS AND ADVANCE THEORY (GREAT), 2026)
Although the adoption of digital payment systems among Indonesian Micro, Small, and Medium Enterprises (MSMEs) has grown rapidly, access to formal bank financing remains relatively limited. Previous studies have primarily examined the direct effects of digital payments on business performance or financial inclusion, while the mechanism through which digital transactions improve financing access has received limited empirical attention. This study aims to examine the mediating role of MSMEs' Financial Profile in the relationship between digital payment adoption and access to bank financing. A quantitative explanatory research design was employed using data collected from 100 MSMEs in Aceh Province, Indonesia. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that digital payments have a positive and significant effect on MSMEs' Financial Profile (β = 0.512, p < 0.001), while MSMEs' Financial Profile positively influences access to bank financing (β = 0.487, p = 0.001). Furthermore, MSMEs' Financial Profile partially mediates the relationship between digital payments and bank financing access (β = 0.249, p < 0.001; VAF = 53.8%). These findings suggest that the contribution of digital payments to financing accessibility is primarily realized through the development of credible and verifiable financial information. This study contributes to the literature by conceptualizing MSMEs' Financial Profile as an empirically measurable mediating construct and proposing the Digital Financial Signaling Mechanism, which explains how digital transaction footprints are transformed into bankable financial information that supports credit assessment. The findings provide practical implications for banks, policymakers, and fintech providers in developing transaction-based alternative credit scoring models to expand financial inclusion for MSMEs.